CT Image Segmentation Based on clustering Methods. - Mohammed, Rand K.; Ajwad, Asmaa A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: image processing of medical images is major method to increase reliability of cancer diagnosis. Methods: The proposed system proceeded into two stages: First, enhancement stage which was performed using of median filter to reduce the noise and artifacts that present in a CT image of a human lung with a cancer, Second: implementation of k-means clustering algorithm. Results: the result image of k-means algorithm compared with the image resulted from implementation of fuzzy c-means (FCM) algorithm. Conclusion: We found that the time required for k-means algorithm implementation is less than that of FCM algorithm.MATLAB package (version 7.3) was used in writing the programming code of our work.